(3GdCYOGO GdeJMGHI hQSGFd GNQis - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3cd YOO eSWM VdYGg YOOGf ChdGf adjS HYOg YOO BNQ ZjQg s
(3BNQgG (B:s
(3hCfg EPG CNP cd LRA dcd hGMO efgeG hLeY Pdc cdg eYkG s
(3ajg YTQI CTcGds
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B217 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B14 s
Keywords: (3GdQjGVjGJs